2016
DOI: 10.1007/978-1-4939-3124-8_21
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Cytoskeleton Proteins in Fish

Abstract: In this chapter, we describe laboratory protocols for rearing fish and a simple and efficient method of extracting and identifying pathogen and host proteins that may be involved in entry and replication of commercially important fish viruses. We have used the common carp (Cyprinus carpio L.) and goldfish (Cyprinus auratus) as a model system for studies of proteins involved in viral entry and replication. The chapter describes detailed protocols for maintenance of carp, cell culture, antibody purification of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Furthermore, the immunogenic and vaccine potentials of several epitopes of CyHV‐3 have been investigated, including Orf12 (Kattlun, Menanteau‐Ledouble, & El‐Matbouli, 2014) which is readily recognized by the immune system of carp and Orf81 for which conflicting evidence exists (Kattlun et al, 2016; Zhou et al, 2014), although little such research has been conducted in goldfish ( Carassius auratus ). In previous reports, our group elucidated pathogen–host interactions in CyHV‐3‐infected C. auratus through the use of monoclonal antibody‐linked pulldown assay followed by electro‐spray ionization mass spectrometry (ESI‐MS) as described in Gotesman, Menanteau‐Ledouble, and El‐Matbouli (2016). C. auratus is a non‐symptomatic carrier of CyHV‐3, and previous studies demonstrated that in C. auratus , several host defence proteins interact with CyHV‐3 (Bergmann et al, 2010; Gotesman, Abd‐Elfattah, Kattlun, Soliman, & El‐Matbouli, 2014).…”
Section: Uniprot Ref #   Role Coverage [%] # Peptides Mw [Kda] Calc Pimentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the immunogenic and vaccine potentials of several epitopes of CyHV‐3 have been investigated, including Orf12 (Kattlun, Menanteau‐Ledouble, & El‐Matbouli, 2014) which is readily recognized by the immune system of carp and Orf81 for which conflicting evidence exists (Kattlun et al, 2016; Zhou et al, 2014), although little such research has been conducted in goldfish ( Carassius auratus ). In previous reports, our group elucidated pathogen–host interactions in CyHV‐3‐infected C. auratus through the use of monoclonal antibody‐linked pulldown assay followed by electro‐spray ionization mass spectrometry (ESI‐MS) as described in Gotesman, Menanteau‐Ledouble, and El‐Matbouli (2016). C. auratus is a non‐symptomatic carrier of CyHV‐3, and previous studies demonstrated that in C. auratus , several host defence proteins interact with CyHV‐3 (Bergmann et al, 2010; Gotesman, Abd‐Elfattah, Kattlun, Soliman, & El‐Matbouli, 2014).…”
Section: Uniprot Ref #   Role Coverage [%] # Peptides Mw [Kda] Calc Pimentioning
confidence: 99%
“…Pulldown assays use antibodies to capture a “bait” protein in an affinity resin, and in the present study, we applied a pulldown assay to investigate the proteins interacting with the Orf149 epitope: Orf149 mAbs were linked to N‐hydroxysuccinimide (NHS)‐activated agarose columns (Gotesman et al, 2016) to capture and identify host proteins interacting with CyHV‐3. Kidney samples of C. auratus previously infected by intraperitoneal injection with 200 µl of CyHV‐3 virus at a concentration of 10 4 TCID 50 (Kattlun et al, 2014, 2016) were lysed using a Tissue Lyser (Qiagen).…”
Section: Uniprot Ref #   Role Coverage [%] # Peptides Mw [Kda] Calc Pimentioning
confidence: 99%
“…Differential transcriptional patterns obtained from qPCR based methods [ 99 , 100 ] can be coupled to protein-based studies [ 101 ] to enhance our understanding of pathogen-host interactions. For protein purification, antibodies raised against the pathogen(s) of interest can be used to capture proteins involved in host-pathogen interactions which are subsequently identified by mass spectrometry [ 102 ]. Such studies have been used to differentiate between host pathogen interactions of susceptible carp versus carrier goldfish for CyHV-3 entry and replication [ 103 , 104 ].…”
Section: Bio Diagnostics/characterizationmentioning
confidence: 99%